Mobility and Ideological Perspective of Asano Akira in Java During Period of Japan Occupation - Syahrur Marta Dwisusilo; Lucitra A. Yuniar (MOZAIK HUMANIORA, 2020)
The period of Japanese occupation for 3 years in Indonesia is sort when compared to the Dutch colonial period. However, at that time it was a critical time for the formation of various ideological thoughts. One of the ideologies that emerged in the Japanese colonial era was the ideology of "Greater Asia", which is known as the ideology of unification of Asia. During the Pacific War, Japanese writers who underwent military service in Indonesia published many of his writings for the purposes of Japanese military propaganda, especially those related to prapaganda of Greater Asia ideology. One of the most active writers in spreading this ideology was Asano Akira. This research clarifies the role of Asano Akira in spreading the ideology of Greater Asia through its activities and mobility in Java with the approach of new historicism and orientalism.